Assessing the prevalence and economic significance of coccidiosis individually and in combination with concurrent infections in Pakistani commercial poultry farms. (24th November 2018) - Rashid, Muhammad; Akbar, Haroon; Bakhsh, Amir; Rashid, Muhammad Imran; Hassan, Muhammad Adeel; Ullah, Rahmat; Hussain, Tahir; Manzoor, Sohail; Yin, Hong
ABSTRACT: Coccidiosis is one of the most economically important diseases of the poultry, around the globe. In order to assess seasonal and age-wise prevalence of coccidiosis individually and with concurrent infections, this study was conducted on commercial poultry farms in and around Multan division, province of Punjab, Pakistan. A total of 28, 126 boilers, 4, 052 layers and 7, 699 golden bird samples, provided by regional farmers and consultants, were examined by microscopy for the diagnosis of coccidiosis. Based on postmortem lesions, several infections including coccidiosis, viral, and miscellaneous diseases were catalogued, whereas samples were cultured to identify concurrent bacterial diseases. Cumulative analysis of this large set of samples revealed a prevalence of 14.16, 11.01, and 19.57% in broiler, layer and golden birds, respectively. Ascaridia galli ( A. galli ) showed a higher prevalence in layer (2.47%) compared to golden (0.21%) birds ( P < 0.01). Amongst all concurrent infections investigated, bacterial infections were identified in highest percentage of samples (59.24%; P < 0.05). The age-wise and season-wise prevalence of coccidiosis and A. galli was found to be significant ( P < 0.05). During the study period, an estimated of 10.69 (coccidiosis) and 0.29 ( A. galli ) million poultry birds were treated or provided prophylaxis and supportive therapy at Pakistani commercial poultry farms. Depending upon the prevailing market conditions, the total economic losses (treatment, prophylaxis, and supportive therapy) from coccidiosis and A. galli were estimated to be US 45, 405.00 and 2, 638.50, respectively, while production (weight and eggs) losses for broiler (US 2, 750, 779.00), layer and golden, young (US 13, 974.98 and 50, 228.76) and adult (US 104.74 and 203.77) were estimated. Unit loss of coccidiosis with concurrent diseases and intestinal worm was estimated to be US 0.005 and 0.01, respectively. These results highlight the potential impact of coccidiosis individually and with concurrent infections on the poultry productivity and will inform farmers, policy makers, and other governmental and non-governmental stakeholders on the use of control and management measures in containing these infections.